Diplodia corticola and Phytophthora cinnamomi : the main pathogens involved in holm oak decline on Caprera Island (Italy) - Linaldeddu, B. T.; Scanu, B.; Maddau, L.; Franceschini, A. (Forest Pathology, 2014)
Since 2008, severe and widespread tree decline and mortality has been observed at the main growing Quercus ilex L. (holm oak) forest on Caprera Island, Italy. To clarify the symptomatology and aetiology of this phenomenon, field surveys and isolations from symptomatic trees were carried out in summer 2010. Affected trees exhibited crown thinning, branch dieback, sunken cankers, epicormic shoots, exudates on branches and trunk, root losses and sudden death symptoms. Four fungal species belonging to Botryosphaeriaceae family, namely Botryosphaeria dothidea, Diplodia corticola, D. seriata and Neofusicoccum parvum, were isolated from cankers on trunk and branches, whereas three species of Phytophthora, namely P. cinnamomi, P. cryptogea and P. gonapodyides, were isolated from fine roots and rhizosphere soil samples. Isolates were identified using both morphological analysis and DNA-based techniques. Pathogenicity trials on holm oak seedlings showed that all the isolated species are pathogenic. D. corticola proved to be the most aggressive species. Our results provide the first evidence for a combined involvement of D. corticola and P. cinnamomi in the aetiology of holm oak decline in Italy and suggest that these pathogens are not only important contributing factors in the onset of long-term tree decline, but also may cause the rapid devastation of extensive oak ecosystems.
Key words by Adriana SilvaKey words by Adriana SilvaThe following values have no corresponding Zotero field: label: APS;Quercus ilex L.;fungus;mortality;pathogens;tree decline
Keywords: APS; Fungus; mortality; pathogens; Quercus ilex L.; tree decline

Phytotoxins produced by the oak pathogen Discula quercina - Maddau, L.; Perrone, C.; Andolfi, A.; Spanu, E.; Linaldeddu, B. T.; Evidente, A. (Forest Pathology, 2011)
Two phytotoxic metabolites, p-hydroxybenzaldehyde and indol-3-aldehyde, were isolated and identified by spectroscopic methods from solid cultures of Discula quercina, an endophytic fungal pathogen frequently associated with oak decline in Italy. In addition, the fungus produced an unusual acyclic keto acid as a major metabolite, which was identified by spectroscopic and chemical methods as 5-oxo-6E,8E-octadecadienoic acid. In leaf puncture assays on Quercus suber and Q. ilex leaves, indol-3-aldehyde proved to be more toxic than p-hydroxybenzaldehyde, while 5-oxo-6E,8E-octadecadienoic acid was inactive even at the highest concentration used (1 mg ml−1). Although indol-3-aldehyde is a known microbial metabolite, its phytotoxic activity has hitherto not been reported. This report is the first to describe the production of phytotoxic compounds by D. quercina.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Discula quercina (voyant); Oak decline; phytotoxic metabolites